Characteristics, secondary transformation and odor activity evaluation of VOCs emitted from municipal solid waste incineration power plant. (15th January 2023) - Sun, Chengyi; Wang, Zhiping; Yang, Yong; Wang, Minyan; Jing, Xianglong; Li, Guoao; Yan, Jing; Zhao, Liyun; Nie, Lei; Wang, Yiqi; Zhong, Yuxi; Liu, Yang
Abstract: Volatile organic compounds (VOCs) emitted from municipal solid waste incineration power plant (MSWIPP) plays a significant role in the formation of O3 and PM2.5 and odor pollution. Field test was performed on four MSWIPPs in an area of the North China Plain. Nonmethane hydrocarbons (NMHCs) and 102 VOCs were identified and quantified. Ozone formation potential (OFP), secondary organic aerosol formation potential (SOAFP), and odor activity of the detected VOCs were evaluated. Results showed that the average concentration of NMHCs and VOCs were 1648.6 ± 1290.4 μg/m 3 and 635.3 ± 588.8 μg/m 3, respectively. Aromatics (62.1%), O–VOCs (16.0%), and halo hydrocarbons (10.0%) were the main VOCs groups in the MSWIPP exhaust gas. VOCs emission factor of MSWIPP was 2.43 × 10 3 ± 2.27 × 10 3 ng/g-waste. The OFP and SOAFP of MSWIPP were 960.18 ± 2158.17 μg/m 3 and 1.57 ± 3.38 μg/m 3, respectively. Acrolein as the dominant VOC species was the major odor contributor with a percentage of odor contribution of 65.9%. Benzene and 1, 2, 4-trimethylbenzene as the dominant VOC species were the main contributors of O3 formation potentials, in which 1, 2, 4-trimethylbenzene was also the main contributors of SOA formation potential. Graphical abstract: Image 1 Highlights: Comprehensive system analysis the VOCs emission character of municipal solid waste incineration power plant. Aromatics and O–VOCs were the key VOCs categories of OFP, SOAFP and odor activity evaluation of MSWIPP emission. Benzene, 1, 2, 4-trimethylbenzene and acrolein were the key VOCs to which need paying special attention.